Copts and Their Political Role in Egypt (1866-1918) - Alsadi, Mohamed D. K.; Hena, Itlal Salem (Humanities Journal of University of Zakho, 2017)
Copts is one of the essential communities of the Egypt ian .It also one of the original communities that has a history goes back to the Egyptian civilization .Because Egypt is a care of history. Civilization and religions it was of a great importance to shed the light on the Christians in Egypt as represented by the Copts .The study Focuses on the Copts Political role in Egypt forts essential importance to show the nature of the Egyptian Society that is unified by their citizenship and Home Loyalty This is well clarified as mentioned in this study by the real representation of the Copts at the Political and administrative sites.